Pengaruh Thin Capitalization, Corporate Risk dan Sales Growth Terhadap Tax Avoidance dengan Kepemilikan Institusional sebagai Variabel Moderasi - Amaliya, Vina; Sudarmanto, Eko (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine the Effect of Thin Capitalization, Corporate Risk and Sales Growth on Tax Avoidance with Institutional Ownership as a Moderating Variable in Energy Sector Companies listed on the (IDX) in 2020-2024. This study uses a quantitative approach. The population in this study includes Energy companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The sampling technique used is Purposive Sampling. Based on the established criteria, 23 company samples were obtained. The type of data used is secondary data obtained from the official website of the Indonesia Stock Exchange. The method used in this study is panel data regression analysis using Eviews 12. The results of this study indicate that simultaneously Thin Capitalization, Corporate Risk, Sales Growth together have an effect on Tax Avoidance and Institutional Ownership has no effect on Tax Avoidance. Partially, Institutional Ownership cannot moderate the relationship between Thin Capitalization and Tax Avoidance, and Institutional Ownership can moderate the relationship between Corporate Risk and Sales Growth on Tax Avoidance.